3a-(2-9b)=

Simple and best practice solution for 3a-(2-9b)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-(2-9b)= equation:


Simplifying
3a + -1(2 + -9b) = 0
3a + (2 * -1 + -9b * -1) = 0
3a + (-2 + 9b) = 0

Reorder the terms:
-2 + 3a + 9b = 0

Solving
-2 + 3a + 9b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 3a + 2 + 9b = 0 + 2

Reorder the terms:
-2 + 2 + 3a + 9b = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 3a + 9b = 0 + 2
3a + 9b = 0 + 2

Combine like terms: 0 + 2 = 2
3a + 9b = 2

Add '-9b' to each side of the equation.
3a + 9b + -9b = 2 + -9b

Combine like terms: 9b + -9b = 0
3a + 0 = 2 + -9b
3a = 2 + -9b

Divide each side by '3'.
a = 0.6666666667 + -3b

Simplifying
a = 0.6666666667 + -3b

See similar equations:

| 50/950 | | 2m+(9m^2+3m)= | | 3x-17=-17+9x | | 7y-24=-15+6y | | 24y+2x=114 | | 4*x-1=X-2 | | 2(3+3x)-7=17 | | 20x-11-14x=3(2x-5)+4 | | t(t-1)=0 | | 0.5x+5=12.5 | | 4x(4+3y)-9(x+2xy)= | | 5(0.5x+2)=22.5 | | 22.5=10+2.5x | | 35.123/100 | | 5(e^2x)=7 | | 10x+23(x-5)=281 | | 6.5/39 | | (-6/-7)x(-5/3)x4 | | 3(x+7)-4x=12 | | -2(x+7)=6x-38 | | 6.2/0.05 | | (2/-5)(8)(-9/3) | | 5[1/2-x]=5/4 | | 9=0.2x*0.2x*0.6x | | 9=0.2x*0.2x*0.06x | | 8h-4h+2=78 | | 1-7x=7x-1 | | 7x+2=12.5 | | X^2+X-110+2(4)=8 | | 16/2=n | | 2(9x+5)=190 | | x^2-15x-44=7x+4 |

Equations solver categories